Tumour-to-tumour metastasis: Rectal adenocarcinoma metastasis to medullary carcinoma of thyroid-Case report and review of the literature - Mahmoud Elsayed; Andrew McCarthy; Marium Khan (Elsevier, 2022)
Tumour-to-tumour metastasis is a rare incidence. Metastasis from colorectal cancer to primary thyroid neoplasm is extremely rare. We report a case of metastatic rectal adenocarcinoma to a medullary thyroid carcinoma. A 64-year-old female patient was diagnosed with rectal adenocarcinoma and treated with chemotherapy and surgery. As part of her follow-up she had whole body CT and PETCT imaging. This identified suspected lung metastasis and a nodule in the thyroid gland. Ultrasound and fine needle aspiration cytology of the thyroid lesion raised the suspicion of medullary thyroid carcinoma. The patient was offered surgery for both lesions in the lung and thyroid. The histopathology of the thyroidectomy specimen revealed a metastasis from a rectal adenocarcinoma within a medullary thyroid carcinoma. We present herein the incidence, clinical presentation, and pathological characteristics of metastatic colorectal cancer to a thyroid gland neoplasm, with a relevant literature review.